To solve the quadratic equation \(-2x^2 - 3x + 2 = 0\) using the quadratic formula, we first identify the coefficients \(a\), \(b\), and \(c\) from the equation in the standard form \(ax^2 + bx + c = 0\):
- \(a = -2\)
- \(b = -3\)
- \(c = 2\)
The quadratic formula is given by:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Now, we will substitute the values of \(a\), \(b\), and \(c\) into the formula.
- Calculate the discriminant (\(b^2 - 4ac\)):
\[ b^2 = (-3)^2 = 9 \]
\[ 4ac = 4 \cdot (-2) \cdot 2 = -16 \]
\[ b^2 - 4ac = 9 - (-16) = 9 + 16 = 25 \]
- Now substitute into the quadratic formula:
\[ x = \frac{-(-3) \pm \sqrt{25}}{2 \cdot -2} \]
\[ x = \frac{3 \pm 5}{-4} \]
Now we will calculate the two possible values for \(x\):
- For \(x = \frac{3 + 5}{-4}\):
\[ x = \frac{8}{-4} = -2 \]
- For \(x = \frac{3 - 5}{-4}\):
\[ x = \frac{-2}{-4} = \frac{1}{2} \]
Thus, the solutions to the equation \(-2x^2 - 3x + 2 = 0\) are:
\[ x = -2, \frac{1}{2} \]
So, you can choose option A:
A. \(x = -2, \frac{1}{2}\)